Cell junctions in the prostate: an overview about the effects of Endocrine Disrupting Chemicals (EDCS) in different experimental models - Scarano, Wellerson R. [UNESP]; Pinho, Cristiane F. [UNESP]; Pissinatti, Lorenzo; Gonçalves, Bianca F. [UNESP]; Mendes, Leonardo O.; Campos, Silvana G.P. [UNESP] (Elsevier, 2018)
Throughout the last decades, increasing exposure to environmental Endocrine Disruptors Chemicals (EDCs) has been associated with the occurrence of male reproductive disorders, such as impairment of prostate development and function, increase of susceptibility to oncogenesis, Epithelial-Mesenchymal Transition and the metastatic invasive potential. Nevertheless, few studies address the mechanisms involved in these alterations, especially those related to cell junctions, which are hormonally regulated and, therefore, possible EDCs targets. The cellular mechanisms discussed in this review are addressed to EDCs actions on tight, gap and adherent junctions and its related genes and proteins, such as claudin-1, -3, -4 and -8, connexin-32 and -43, E-cadherin and β-catenin, respectively. The impairment of cell junction function, mainly due EDCs exposure during the prostate's critical window of development, can corroborate to acquire a mesenchymal phenotype by epithelial cells and the prostate microenvironment becomes susceptible to development of lesions in the latter stages of life.
Keywords: Cell junctions; EDCs (Endocrine Disrupting Chemicals); EMT (epithelial-mesenchymal transition); Toxicants